2017
DOI: 10.1007/s10943-017-0448-3
|View full text |Cite
|
Sign up to set email alerts
|

Family Interdependence, Spiritual Perspective, Self-Transcendence, and Depression Among Korean College Students

Abstract: The purpose of this study was to examine the mechanisms that might account for the effects of spirituality and self-transcendence on Korean college students' depression among 197 Korean fathers, mothers, and children. A structural equation analysis indicated that spiritual perspective related to lower depression through the mediating pathway of self-transcendence for individuals. Mothers' spiritual perspective and self-transcendence related to their children's depression through the mediating pathway of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…This study used family data from a larger study that examined family and individual factors related to depression in the families of Korean college students. An earlier study ( 17 ) reported the intergenerational transmission of spirituality and its relationship to depression in the families of Korean college students using only the Spiritual Perspective Scale (SPS) ( 24 ), Self-Transcendence Scale (STS) ( 25 ), and CES-D ( 8 ). This study used all study variables and focused on the analysis results of the ML models to develop the best predictive model by identifying the best set of variables using 171 family data (513 individuals).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study used family data from a larger study that examined family and individual factors related to depression in the families of Korean college students. An earlier study ( 17 ) reported the intergenerational transmission of spirituality and its relationship to depression in the families of Korean college students using only the Spiritual Perspective Scale (SPS) ( 24 ), Self-Transcendence Scale (STS) ( 25 ), and CES-D ( 8 ). This study used all study variables and focused on the analysis results of the ML models to develop the best predictive model by identifying the best set of variables using 171 family data (513 individuals).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have shown that family dynamics affect the susceptibility of college students to depression and its persistence (16)(17)(18)(19). Kim et al (17) examined the relationship between the depression of parents and that of their children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ademais, uma tarefa desenvolvimental da família, em especial se o ingresso na universidade se atrela à saída de casa, é oferecer apoio e criar condições para que o jovem possa separar-se sem romper os laços afetivos e sem perder ou ter ameaçada sua identidade enquanto membro da família 10 . Questões de gênero, estilos parentais, relação conjugal dos pais, espiritualidade, interações entre familiares e diferentes características da família têm sido investigadas na busca de sistematizar informações sobre como tais elementos se conectam a problemas de saúde mental entre jovens universitários [11][12][13][14] . Entretanto, a maioria dos estudos com universitários prioriza a descrição de um perfil de estudantes circunscrito a uma determinada instituição de nível superior, de modo que as variáveis sociodemográficas são explicitadas, mas não investigadas em termos de suas possíveis associações com aspectos relacionados à saúde ou mesmo com variáveis de funcionamento familiar 15 .…”
Section: Introductionunclassified
“…C ouples or families can function as significant resources for supporting mental health. [1][2][3] Studies have indicated that healthy marital and family relationships prompt social support, enhance selfesteem, and reinforce healthier behaviors in general, leading to the promotion of mental health and an ability to cope with stress. 2,4 Two theories of family interdependence 2,5,6 and cross-over stress [7][8][9][10][11] have explained how marital and family relationships influence mental health.…”
Section: Introductionmentioning
confidence: 99%